Modernization of Women's Education in Social Change in The Sultanate of Siak Sri Indrapura, Riau 1927-1950 - Arianingrum, Nabila; Martina Safitry (Journal of Islamic History and Manuscript, 2025)
This study explores the modernization of women's education in the Siak Sultanate during the early 20th century, focusing on the Sultanah Latifah School and Madrasatun Nisa’. The research addresses how women's education became a medium for social transformation within traditional Malay society amid colonial influence, Islamic reform, and local educational awareness. It investigates the social context and development of women's education in Siak Sri Indrapura, employing a qualitative historical method. Data were collected through archival research, oral history, and field observations. Sultanah Latifah School, initiated by Sultan Syarif Kasim II, adopted a Western-oriented curriculum including reading, writing, arithmetic, Dutch, etiquette, and Islamic studies. In contrast, Madrasatun Nisa’ emphasized Islamic modernist teachings, such as Arabic, women’s jurisprudence (fiqh), ethics, and reformist thought. These institutions represented a significant shift in traditional female roles, fostering public engagement and intellectual development. The findings highlight that both schools blended local customs, Islamic values, and modern pedagogy, marking a pioneering effort in localized women's educational reform. This modernization promoted not only religious and cultural continuity but also opened avenues for broader societal participation by women. The study concludes that the Siak Sultanate played a key role in advancing women's education within a framework respectful of tradition yet oriented toward progress. It emphasizes the need to preserve such historical educational models and to further explore the legacy of female graduates in shaping modern society. The integration of regional history into educational curricula is also recommended to enrich contemporary understanding